Time-Resolved Resonance Raman Studies of Radicals From 4-Aminoresorcinol as Models for the Active Site Radical Intermediate in Copper Amine Oxidases. Issue 1 (1999) - Bisby, Roger H.; Johnson, Steven A.; Parker, Anthony W.; Tavender, Susan M.
Abstract : Radicals formed by one-electron oxidation of 4-aminoresorcinol have been studied as models for the active site free radical intermediate which forms as a stable product during anaerobic incubation of amine oxidases with amine substrates. Pulse radiolysis shows that the radical undergoes ionisations with pKa 's of 3.4 and 6.4. Although the two deprotonated forms are difficult to distinguish by absorption spectroscopy, they have clearly different resonance Raman spectra. Comparison with the resonance Raman spectrum of the enzyme intermediate shows it to be the singly deprotonated form of the radical.